Antimicrobial Activity of Some Trichoderma spp. against Different Kinds of Fungal and Bacterial Isolates - Omar Al-Obaidy (College of Education for Pure Sciences, 2019)
Two types of the fungus Trichoderma were chosen, these are T.viride and T.harzianum. The activity of these fungi were tested against different kinds of plant and human pathogenic fungi. After screening , the fungus T.harzianum was selected because it showed highest efficiency in its antagonistic activity than T.viride. It was also tested against other kinds of the plant and human pathogenic fungi and the fungus Macrophomina phaseolina was the most sensitive toward T.harzianum. In addition, the active compound from the fungus T.harzianum was extracted then tested against different types of pathogenic fungi and different types of pathogenic Gram positive and negative bacteria which showed different values of antagonistic activity. Bacillus subtilis was the most sensitive to the extract. Thus, many tests could be done to ensure the safety of this fungus (and its extract) and that is not toxic and to ensure its antagonistic activity toward the studied microbes inside the living body (In-Vivo), and then it could be used as good alternative to the chemicals that have side effects.